Green approaches in Hong Kong’s fast-food restaurants and its effects on corporate image - Wong, Anthony (Journal of Research in Marketing (ISSN: 2292-9355), 2016)
Previous studies have found a positive linear relationship between corporate social responsibility (CSR) and corporate image. CSR was found can improve an organisation’s competitive edge and sustainability. In addition, CSR and the concept of 3R (reduce, reuse, and recycle) can enhance the corporate image and its effect on the performance of fast-food marketing. This research adopted a positivism paradigm and quantitative cross-sectional approach with a sampling frame comprising customers of Hong Kong’s fast-food restaurants which are facing keen competition. 350 sets of data were collected from customers by using a questionnaire to measure four constructs that were adopted from previous studies to identify the relationships between various antecedents and to test four hypotheses. The research found that all direct relationships between CSR and corporate image, and similarly between 3R and corporate image, were found significant and positive. It is believed that 3R plays a better long-term role rather than CSR activities, such as philanthropic acts that help the community and support charities. The research verifies that CSR and 3R practices are appropriate competitive advantage tools to enhance corporate image, which will ultimately benefit the fast-food industry in Hong Kong.